Мотив переименования персонажа в произведениях Андрея Платонова - Jablokov, Evgenij (Wiener Slawistischer Almanach, 2022)
The subject of this article is the renomination, or renaming, of characters in Platonov’s works. The analysis proves that the instances of renaming imply a “repersonification”, a true change of personality, a definitive internal metamorphosis or transformation into another person. Thus, renaming is not an external, formal act; it is connected with existential problems and, ultimately, with the general conception of Platonov’s world. Examining the practice of renomination allows us to see more clearly the fundamental problems of Platonov’s poetics, the essence of his language and philosophical thinking. Onomastic collisions demonstrate in a peculiar way the “relativity” of the writer’s Word – a Word that is ambivalent in combining aphorism and auto-parody, that is able to reflect the world’s deepest essence while remaining “internally” ready to turn into its opposite.